Analytic model for calculation of soil temperature and heat balance of bare soil surface in solar greenhouse. (1st January 2023) - Deng, Lianhua; Huang, Lin; Zhang, Ying; Li, Angui; Gao, Ran; Zhang, Linhua; Lei, Wenjun
Highlights: The model can predict soil temperatures in a solar greenhouse. The heat gain and loss of solar greenhouse soil surface are calculated. The effect of water evaporation intensity on the soil temperature are analyzed. Abstract: This study establishes a soil temperature model of a solar greenhouse, which takes into account the soil water evaporation, solar radiation, thermal radiation and convective heat transfer on the soil surface. The model is utilized to obtain the mathematical function of soil temperature distribution according to solar radiation and air temperature in a solar greenhouse. The model is validated in two greenhouses with and without plants. Based on the model, the heat gain and loss of solar greenhouse soil are calculated. The results show that the heat accumulated by the greenhouse soil is mainly by absorbing solar radiation during the day and the heat lost by the greenhouse soil is mainly by water evaporation during the day and thermal radiation at night. Then, according to the small convective heat transfer between soil and air in the solar greenhouse, the solar-air temperature calculation equation is simplified, so that the simplified model can predict the soil temperature based on solar radiation and outdoor air temperature, which provides an important soil boundary condition for the solar greenhouse thermal model and CFD prediction. Finally, the evaporation coefficient is proposed to characterize the effect of water evaporation intensity on the soil temperature in a solar greenhouse. In this case, the average soil temperature increases by about 2℃ for every 0.1 decrease in evaporation coefficient.